An Empirical Study to Predict the Self-Employment Intention of Engineering Students Using EAO Model in Kerala - Sonia Katherin Mathew and Johney Johnson (Commerce Spectrum, 2014)
India produces more than five lakh engineers every year but very few of them are employed, the rest are unemployed. The statistics have shown that the market is oversupplied with young and inexperienced engineering graduates .The present study is mainly focusing on engineering graduates in Kerala. In Kerala there are more than 120 engineering colleges and every year more than 35,000 students pass out with engineering qualification but the question is how many of them are employed? Since career opportunities are less in Kerala they migrate to distant places in search of greener pastures. To solve the unemployment issue among graduates, the only solution is self- employment. Hence, it is important to know the self-employment intentions of engineering graduates. In the present study EAO model is used to understand the engineering graduate attitudes toward entrepreneurship and their relationship with self-employment intentions. A survey approach was adopted in the study. The sample size taken for the study was 300 students from different engineering colleges in Kerala on the basis of convenience. The results show that personal control and self-esteem have significant and positive relationships with self- employment intention. Meanwhile achievement and innovation were found to have no significant relationship with self-employment intention. These findings provide important insight to promote and produce a positive image of entrepreneurship as a career.